2018
DOI: 10.1111/apt.14988
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: which inflammatory bowel disease patients should be screened for Epstein‐Barr virus infection?

Abstract: Linked Content This article is linked to de Francisco et al papers. To view these articles visit https://doi.org/10.1111/apt.14933 and https://doi.org/10.1111/apt.14502.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Among 37 seronegative patients, we found that the seroconversion rate was 29.7% (95% CI: 16.2%‐45.9%) after a mean of 47.5 months. There were no differences in seroconversion rates between patients 35 years or younger and those older than 35, or between men and women . Therefore, based on the previous results, we believe that the risk of these complications is not limited to young males but is linked to patients’ seronegative status, regardless of age or gender.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Among 37 seronegative patients, we found that the seroconversion rate was 29.7% (95% CI: 16.2%‐45.9%) after a mean of 47.5 months. There were no differences in seroconversion rates between patients 35 years or younger and those older than 35, or between men and women . Therefore, based on the previous results, we believe that the risk of these complications is not limited to young males but is linked to patients’ seronegative status, regardless of age or gender.…”
mentioning
confidence: 68%
“…We appreciate the editorial by Hans and Scott regarding our study on the seroprevalence, seroconversion and complications related to Epstein‐Barr virus (EBV) infection in patients with inflammatory bowel disease (IBD) . We agree that it is necessary to have as much information as possible regarding the epidemiology of EBV infection in patients with IBD so that the design of cost‐effectiveness models for EBV screening in such patients is based on accurate data.…”
mentioning
confidence: 99%
“…Notably, the exposure to EBV in adulthood is almost universal, and the incidences of hematological malignancies in IBD are rare. In the cost-bene t analysis, it seems that the value of EBV detection before the IBD patient starts treatment is limited [9,[19][20][21]. Our results suggest that it is important not only to consider the activation of EBV by immunosuppressive drugs that can lead to related malignant tumors but also to understand the relationship between EBV infection and the severity of IBD.…”
Section: Discussionmentioning
confidence: 93%